Starch Functional Properties and Resistant Starch from Foxtail Millet [Setaria italica (L.) P. Beauv] Species - Bangoura, Mohamed Lamine; Nsor-Atindana, John; Ming, Zhou Hui; Wei, Peng; Mothibe, Kebitsamang Joseph; Xue, Zhu Ke (Pakistan Journal of Nutrition, 2012)
The study evaluated physicochemical and content of Resistant Starch (RS) of starches isolated from defatted white foxtail millet and yellow foxtail millet by alkaline extraction. The characteristic of the isolated starches were compared with those of commercial corn starch (CCS). The extraction yielded 42.10% and 39.29% (dry basis) of starch respectively, for white and yellow foxtail millets. The amylose content was highest (35.80mg g-1) in the Yellow Foxtail Starch (YFS) followed by White Foxtail Starch (WFS) which recorded 34.92mg g-1 and CCS (33.98mg g-1) with significant difference (p<0.05). The amylopectin was found in trace amounts for both WFS and YFS, whereas highest value of carbohydrate was found in CCS (98.59 mg g-1) followed by WFS (98.03mg g-1) and YFS (82.79mg g-1). Microscopic examination showed that all starch granules had sizes ranging from 20 to 50 μm with variable irregular shapes. Millet starch indicated highest degree of syneresis and gel consistency. Swelling and solubility increased as temperature increased from 60 to 95°C. Pasting viscosities and maximum peaks were CCS (75.34°C, 3307cP), WFS (76.09°C, 3321cP) and YFS (76.10°C, 3322cP). The RS in raw defatted and hot boiled starches were (15.77-9.17%) in CCS, (13.35-7.46%) WFS and (14.56-8.24%) YFS, respectively and showed a significant difference (p<0.05) among samples.